‘Businessology’ and Social Work - John Harris (Social Work and Society, 2003)
There is a spectre stalking social work in many countries of the world. That spectre is the belief that social work needs to be reshaped in the image of capitalist business enterprises, what we might term business ideology or ‘businessology’. Within that belief, the explicit or implicit assumption is that social work should, as far as possible, function as though it were a commercial business concerned with making profits. In those countries most affected, the culture of capitalism has colonised social work as business thinking and practices have been introduced. The embrace of businessology in social work is presented as a neutral trend, to which all social workers can be committed, namely, the modernisation of social work and making it more efficient through the application of distinctive and valuable expertise.